Use of webcasting technology in teaching higher education - Md. Yunus, Aida Suraya; Kasa, Zakaria; Asmuni, Azizan; Abu Samah, Bahaman; Napis, Suhaimi; Mohd Yusoff, Mohd Zul; Khanafie, Mohd Rizal; Abdul Wahab, Hasmah (Shannon Research Press, 2006)
Schools and universities all over the world are continuously exploring ways to use the web technology in improving teaching effectiveness. The use of course web pages, discussion groups, bulletin boards, and e-mails have shown impact on teaching and learning in significant ways, across all disciplines. e-Learning has emerged as an alternative to traditional classroom-based education and training, especially for distance learning programs. Thus, this research study was conducted to investigate the effectiveness of the implementation of webcasting technology in teaching in higher education. In this research, three modes of webcasting lectures were experimented on three different groups of students, using the pre test-post test-control group experimental design. The modes are live streaming, pre-recorded streaming and video on demand (VOD). The group that attended the face-to-face lecture acts as the control group. The overall analysis showed that the students who went through the VOD group showed the most gain in the tests.